Elaboración de un manual para la práctica deportiva de fútbol de los estudiantes de quinto y sexto años de educación básica del centro educativo municipal “Alicia Marcuard de Yerovi” del cantón Salcedo, provincia de Cotopaxi, durante el año lectivo 2011 - 2012 - Arias Jiménez, Mercedes Elizabeth (2015)
The present work was performed, was applied research students in fifth and sixth years of Basic Education Municipal School" Alicia Marcuard of Yerovi" on the knowledge that the sport of football in order to give an alternative proposal. The methodology was field research where the needs of the institution at the time of playing football was palpated in which the teacher has a lot of difficulty in teaching the technical fundamentals, because you need to implement a methodology for teaching-learning of football. The results which thrown they realized that the little sport practice know ledge, the pre-game sport show it to the background, the sport activities are noticed an absolute mess when the class because children are not showing interested for football. In conclusion....